Is Natural Selection still have to be Regarded A Foundation Stone of Evolutionary Process? - Andrey I. Granovitch (Journal of Evolutionary Science, 2018)
Natural selection is a buzzword used to describe the main driving force of evolution. Its creative role is believed to be based on: a) an unlimited variety of organisms caused by hereditary variation and b) a direct connection between hereditary changes and their phenotypic expression. These are the two requirements that can lead to the genetically based changing modalities of characters through “iterations” of natural selection in the series of successive generations. Are these two requirements fulfilled in the nature, however? The present study focuses on the analysis of these two “foundation stones” of natural selection. Firstly, hereditary variation is shown to be essentially non-homogenous. New hereditary characteristics of individuals fall onto a narrow “strip of land” in the sea of potential possibilities. Secondly, the consequences of changes in the genotype of an organism are involved into a system of hierarchical multiple compensation, from the molecular to the biocenotic level. In a way, the signal of hereditary change passes through a series of “system filters” at epigenetic, ontogenetic, physiological, behavioural, populational and biocenotic level. Each filter is represented by multiple feedbacks maintaining the integrity of systems at each level and at all the hierarchical levels taken together. It is in these “system filters” the adaptive nature of characters is formed representing the every individual as a subject to the Law of Multilevel Self-Organization. The emerging understanding of this provides a strong reason to change the evolutionary paradigm from the mainly selectogenetic to the mainly orthogenetic one.
Keywords: natural selection